Antiviral composite polylactic acid and application thereof in melt-blown non-woven fabric
By loading silver-containing nanoparticles with polylactic acid and blending them with polylactic acid on Elostone nanotubes and meltblown, a composite polylactic acid meltblown cloth with antiviral and excellent filtration performance was prepared, which solved the antiviral of existing PLA materials. Capacity and environmental safety issues achieve degradable and efficient virus protection effects.
Patent Information
- Application Number
- CN202310726762.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
AI Technical Summary
The existing PLA meltblown nonwoven materials lack viral resistance, poor mechanical properties and filtration performance, and the matrix materials are not degradable, resulting in insufficient environmental pollution and biosafety.
The silver-containing nanoparticles were loaded on the Eloshima nanotube, melted and blended with polylactic acid and melted and melted to prepare a composite polylactic acid meltblown cloth with antiviral effects, which improved its dispersion, mechanical properties and filtration properties. .
It achieves good degradability, uniform antiviral properties and excellent filtration performance of polylactic acid meltblown cloth, reduces environmental pollution and meets the protection needs of antiviral materials.
Smart Images

Figure HDA0004293144650000011 
Figure HDA0004293144650000012 
Figure HDA0004293144650000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of meltblown fabrics, and in particular to an antiviral composite polylactic acid and an application of the composite polylactic acid in preparing a meltblown nonwoven fabric. Background Art
[0002] The new coronavirus and influenza A virus have placed a huge burden on current medical protection and other fields, and the ability to defend against these threats on a large scale has become a daunting task. Masks have become the most effective protective equipment in daily and medical environments. However, there are currently no antiviral masks that can target respiratory viruses such as the H1N1 influenza virus.
[0003] As a key protective material in masks, meltblown fabrics have been widely used in disposable medical, health care, absorption and filtration materials due to their fluffy porous structure and high specific surface area. With the rapid development of biodegradable polymers, polylactic acid (PLA) has shown great potential to replace widely used petroleum-based meltblown nonwoven materials such as polypropylene (PP) and polyethylene terephthalate (PET). Therefore, PLA meltblown nonwoven materials also show great commercial market potential. However, the current PLA meltblown nonwoven materials basically have no antiviral ability, and their mechanical properties and filtration properties are poor.
[0004] At present, meltblown fabrics are mostly made of polypropylene as the base material, and electret masterbatch, antiviral agent, lubricant, dispersant, stabilizer, etc. are added to prepare a meltblown fabric. The base material polypropylene is not degradable and easily causes environmental burden after being discarded. The electret masterbatch and antibacterial and antiviral agent are added separately, resulting in uneven distribution. In addition, a variety of additives are added, resulting in poor processability and biosafety that needs to be improved. Summary of the invention
[0005] To solve the above problems, the present invention provides an antiviral composite polylactic acid, in which silver-containing nanoparticles are loaded on halloysite nanotubes (HNTs), and then melt-blended and melt-blown with polylactic acid PLA in sequence to obtain composite polylactic acid and melt-blown cloth with antiviral effects. Silver-containing nanoparticles have good antiviral properties, so that loading them on HNTs can improve their dispersibility and the uniformity of the material, and HNTs can improve the filterability and mechanical properties of the composite polylactic acid. An antiviral composite polylactic acid with excellent comprehensive performance can be prepared through a simple process to meet people's use needs in protecting against viruses.
[0006] The first aspect of the present invention aims to provide an antiviral composite polylactic acid, which comprises polylactic acid (PLA) and halloysite nanotubes (HNTs) loaded with silver nanoparticles.
[0007] The mass fraction of the silver nanoparticle-loaded halloysite nanotubes in the antiviral composite polylactic acid is 0.6-2.4wt%, preferably 0.7-1.8wt%, and more preferably 0.8-1.2wt%.
[0008] The second aspect of the present invention aims to provide a method for preparing the antiviral composite polylactic acid, which comprises melt-blending halloysite nanotubes loaded with silver nanoparticles with polylactic acid to obtain a composite masterbatch, and then mixing the composite masterbatch with polylactic acid and melt-blowing the mixture to obtain the antiviral composite polylactic acid.
[0009] Preferably, the method specifically comprises the following steps:
[0010] Step 1. adding a silver compound solution to a solution containing a precipitant and HNTs, stirring the solution to react, and obtaining halloysite nanotubes loaded with silver nanoparticles;
[0011] Step 2. melt-blending PLA and halloysite nanotubes loaded with silver nanoparticles to obtain a composite masterbatch;
[0012] Step 3. Add the composite masterbatch into PLA for melt-blowing to obtain antiviral composite polylactic acid, that is, antiviral composite polylactic acid melt-blown cloth.
[0013] The third aspect of the present invention aims to provide the use of the antiviral composite polylactic acid as a meltblown cloth to make protective equipment for filtering out new coronaviruses and influenza viruses, such as filtering out influenza A (H1N1) virus.
[0014] The protective equipment uses meltblown cloth as filter cloth, such as respiratory masks, masks, etc.
[0015] The antiviral composite polylactic acid and its preparation method provided by the present invention have the following beneficial effects:
[0016] (1) In the present invention, polylactic acid is used as the base material, which has good degradability. Protective articles such as masks are used in large quantities, which can achieve the degradation of waste products and reduce environmental pollution. In addition, polylactic acid has good biosafety, which is more conducive to people's use.
[0017] (2) In the present invention, silver-containing nanoparticles are loaded on HNTs and evenly distributed in the prepared antiviral composite polylactic acid. The silver-containing nanoparticles have good antiviral properties, so that the melt-blown cloth formed by the antiviral composite polylactic acid has uniform antiviral properties.
[0018] (3) In the present invention, HNTs loaded with silver nanoparticles are added to polylactic acid. SiO2 in HNTs has excellent charge storage capacity and is widely used in melt-blown nonwoven materials to improve their filtration performance. At the same time, due to the excellent aspect ratio of HNTs, the melt-blown nonwoven materials have good mechanical properties. And HNTs, as a good carrier of functional particles, can be coupled with antiviral silver nanoparticles to improve their dispersibility.
[0019] (4) The process of the antiviral composite polylactic acid preparation method provided in the present invention is easy to promote in industrial production, the preparation steps are simple and easy to control, and can produce melt-blown cloth with good mechanical properties, antiviral properties and uniform performance, thereby meeting people's usage requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 SEM images of HNTs@Ag3PO4 nanoparticles prepared in Example 1 of the present invention and pure Ag3PO4 nanoparticles prepared in Comparative Example 1 are shown;
[0021] Figure 2 The stress-strain curves of the melt-blown nonwoven fabric HNTs@Ag3PO4 / PLA prepared in Example 2 of the present invention and the PLA melt-blown nonwoven fabric prepared in Comparative Example 2 are shown;
[0022] Figure 3 Curves showing the filtration efficiency of the melt-blown nonwoven fabric HNTs@Ag3PO4 / PLA prepared in Example 2 of the present invention and the PLA melt-blown nonwoven fabric prepared in Comparative Example 2 as a function of the particle size of the DOP aerosol;
[0023] Figure 4 (a) Figure 4 (c) Cell culture photos of PLA meltblown nonwoven fabric and HNTs@Ag3PO4 / PLA meltblown nonwoven fabric without the addition of SCDLP solution of influenza A (H1N1) virus, respectively; Figure 4 (b) Figure 4 (d) Cell culture photos showing the influenza A (H1N1) virus liquid in PLA meltblown nonwoven fabric and HNTs@Ag3PO4 / PLA meltblown nonwoven fabric after being used to inoculate cultured cells. DETAILED DESCRIPTION
[0024] The present invention will be further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present invention will become more clear and distinct.
[0025] The invention provides an antiviral composite polylactic acid, which comprises polylactic acid (PLA) and halloysite nanotubes (HNTs) loaded with silver nanoparticles.
[0026] The mass fraction of the silver nanoparticle-loaded halloysite nanotubes in the antiviral composite polylactic acid is 0.6-2.4wt%, preferably 0.7-1.8wt%, and more preferably 0.8-1.2wt%. When the content of silver nanoparticles is low, the antiviral effect cannot be achieved. When the content of silver nanoparticles is too high, the spinnability of the meltblown cloth is reduced and it cannot be spun smoothly.
[0027] The silver-containing nanoparticles are selected from silver salt nanoparticles, preferably selected from water-insoluble and alcohol-soluble silver salt nanoparticles, such as Ag3PO4 nanoparticles, AgCl nanoparticles, Ag2SO4 nanoparticles, and more preferably Ag3PO4 nanoparticles.
[0028] The present invention also provides a method for preparing the antiviral composite polylactic acid, which comprises melt-blending halloysite nanotubes loaded with silver nanoparticles with polylactic acid to obtain a composite masterbatch, and then mixing the composite masterbatch with polylactic acid and melt-blowing the mixture to obtain the antiviral composite polylactic acid.
[0029] Preferably, the method specifically comprises the following steps:
[0030] Step 1. Add a silver compound solution into a solution containing a precipitant and HNTs, stir and react, and obtain halloysite nanotubes loaded with silver nanoparticles.
[0031] The silver compound is selected from water-soluble silver compounds, such as silver nitrate, silver acetate, water-soluble silver complexes, and the like.
[0032] The precipitant is selected from one or more of water-soluble chlorides, water-soluble sulfates, water-soluble phosphates and water-soluble monohydrogen phosphates, preferably selected from one or more of water-soluble monohydrogen phosphates, and more preferably selected from one or more of Na2HPO4, K2HPO4 and (NH4)2HPO4.
[0033] In the silver compound solution, the solvent is selected from one or more of water, alcohol solvents, ether solvents and ester solvents, preferably selected from one or more of water and glycol solvents, and more preferably a mixed solvent of water and ethylene glycol; in the mixed solvent, the volume ratio of water to ethylene glycol is (8-18):6, preferably (8-15):6, and more preferably (10-12):6; the concentration of the silver compound is (0.4-1.2) mol / L, preferably (0.5-1.0) mol / L, and more preferably (0.6-0.8) mol / L, based on the molar amount of silver therein.
[0034] In the solution containing the precipitant and HNTs, the solvent is selected from one or more of water, alcohol solvents, ether solvents and ester solvents, preferably selected from one or more of water and glycol solvents, and more preferably a mixed solvent of water and ethylene glycol; in the mixed solvent, the volume ratio of water to ethylene glycol is (50-110):20, preferably (60-100):20, and more preferably (70-90):20.
[0035] In the solution containing the precipitant and HNTs, the molar mass ratio of the precipitant to the HNTs is (0.002-0.007) mol:0.8 g, preferably (0.003-0.006) mol:0.8 g, and more preferably (0.004-0.005) mol:0.8 g.
[0036] The molar mass ratio of the silver compound to the HNTs is (0.01-0.06):0.8 g, preferably (0.01-0.04):0.8 g, and more preferably (0.01-0.02):0.8 g.
[0037] The reaction temperature is 10-40°C, preferably 15-35°C, and the reaction time is 1-4h, preferably 2-3h.
[0038] Preferably, the reaction is carried out under light-shielding conditions; the silver compound solution is slowly added to the solution containing the precipitant and HNTs.
[0039] After the reaction is completed, the solvent is removed, washed, dried, and ground to obtain halloysite nanotubes loaded with silver nanoparticles. The average length of the halloysite nanotubes loaded with silver nanoparticles is 100-2000nm, preferably 400-1000nm, and more preferably 600-800nm. HNTs are used as carrier materials. If the length is too long, the spinneret may be blocked. If the length is too short, it cannot effectively load the silver nanoparticles, and the improvement of the mechanical properties of the melt-blown cloth is limited.
[0040] In the halloysite nanotubes loaded with silver nanoparticles, the average particle size of the silver nanoparticles reaches 60-210nm, preferably 80-180nm, and more preferably 100-150nm. The smaller the particle size of the silver nanoparticles, the more conducive it is to improving the antiviral performance of the antiviral composite polylactic acid. It has good antiviral performance and dispersibility within the above particle size range and is easy to prepare.
[0041] Step 2: melt-blending PLA and halloysite nanotubes loaded with silver nanoparticles to obtain a composite masterbatch.
[0042] In step 2, PLA and halloysite nanotubes loaded with silver nanoparticles are first dried at a temperature of 70-90° C. for a drying time of 10-14 h, preferably by vacuum drying.
[0043] The melt blending temperature is 150-225° C., preferably 160-215° C., and more preferably 170-205° C. Melt blending is preferably carried out in a molding extruder, such as a twin-screw extruder. When the blending temperature is low, the viscosity of PLA is large, and the halloysite nanotubes containing silver nanoparticles cannot be effectively dispersed in PLA. As the blending temperature increases, PLA gradually degrades. If the blending temperature is too high, PLA will be completely thermally degraded.
[0044] In the composite masterbatch, the mass fraction of the halloysite nanotubes loaded with silver nanoparticles is 4-18wt%, preferably 6-15wt%, and more preferably 8-12wt%. When the content of the halloysite nanotubes containing silver nanoparticles in the masterbatch is low, the distribution difference in the meltblown cloth is large, and there are blank areas of silver nanoparticles, which makes it difficult to play a comprehensive antiviral role. When the content of the halloysite nanotubes containing silver nanoparticles in the masterbatch is large, it is easy to agglomerate, reduce its photocatalytic activity, and affect the antiviral performance of the meltblown cloth.
[0045] Step 3. Add the composite masterbatch into PLA for melt-blowing to obtain antiviral composite polylactic acid, that is, antiviral composite polylactic acid melt-blown cloth.
[0046] In step 3, PLA and composite masterbatch are first dried at a temperature of 70-90° C. for a drying time of 10-14 h, preferably by vacuum drying.
[0047] The mass of the composite masterbatch is 4-24% of the total mass of PLA and the composite masterbatch, preferably 6-18%, and more preferably 8-12%. When the content of the composite masterbatch is low, the antiviral effect cannot be achieved. When the content of the composite masterbatch is too high, the spinneret is easily blocked, the spinnability of the meltblown cloth is reduced, and the spinning cannot be smooth.
[0048] The melt-blowing is performed using a melt-blown nonwoven machine. During the melt-blowing process, the melting temperature is 175-215°C, preferably 180-205°C, more preferably 185-195°C, and the spinning temperature of the spinneret is 220-250°C, preferably 225-245°C, more preferably 230-240°C. A lower melting or spinning temperature affects the spinning state of PLA, resulting in high viscosity and inability to reel. At a higher melting or spinning temperature, PLA is prone to degradation and the melt-blown fabric has a lower strength.
[0049] The present invention also provides the use of the antiviral composite polylactic acid as a melt-blown cloth to make protective equipment for filtering out the new coronavirus and influenza virus, such as filtering out influenza virus A (H1N1).
[0050] The protective equipment uses meltblown cloth as filter cloth, such as respiratory masks, masks, etc.
[0051] Example
[0052] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.
[0053] Example 1
[0054] 1.71 g (about 0.0048 mol) of Na2HPO4·12H2O and 0.8 g of halloysite nanotubes (HNTs) (manufactured by Sigma-Aldrich, USA, model 685445, length 600-800 nm) were added to 100 ml of a mixed solution of deionized water and ethylene glycol (the volume ratio of deionized water to ethylene glycol was 80:20). The solution was ultrasonicated for 10 min and magnetically stirred for 30 min to obtain a mixed solution A.
[0055] At room temperature, grind silver nitrate (AgNO3) particles into fine powder, weigh 2.448g (about 0.0144mol), add it to a mixture of 20ml deionized water and ethylene glycol (volume ratio of the two is 13.3:6.7), and stir magnetically for 30min to obtain a silver nitrate solution. Use a peristaltic pump to slowly add the silver nitrate solution to the mixed solution A, the peristaltic pump flow rate is 2ml / min, and stir magnetically for 2h in a dark state.
[0056] After the reaction, the reaction solution was centrifuged at 4000 rpm for 5 min, and the solid was washed 3-5 times with ethanol, and then dried at 60°C for 6 hours and ground to obtain halloysite nanotubes loaded with silver nanoparticles (HNTs@Ag3PO4 nanoparticles).
[0057] Example 2
[0058] Polylactic acid PLA (Total Cobien, model 9024, viscosity average molecular weight 72000 g / mol) and HNTs@Ag3PO4 were placed in a vacuum oven at 80°C and dried for 12 hours.
[0059] PLA and HNTs@Ag3PO4 (the content of HNTs@Ag3PO4 in the mixture is 10wt%) are melt-blended using a twin-screw extruder. The temperatures of each zone (Ts1, Ts2, Ts3, Ts4, Ts5 and Ts6) of the twin screw are 180, 190, 200, 190, 185 and 175°C, respectively, and the screw speed is 50r / min. The extrudate is cooled in a water bath to obtain HNTs@Ag3PO4 composite masterbatch.
[0060] PLA and HNTs@Ag3PO4 composite masterbatch were dried at 80℃ in a vacuum oven for 12h. PLA and HNTs@Ag3PO4 masterbatch were mixed for melt-blowing, and the content of HNTs@Ag3PO4 composite masterbatch in the mixture was 10wt%. The temperatures of each zone (Ts1, Ts2, Ts3, head, metering pump and spinneret) of the melt-blown nonwoven machine were set to 185, 190, 190, 190, 195, 210 and 235℃, respectively, the hot air temperature was 215℃, the curtain speed was 25Hz, and the wind speed was 35Hz. The mixture of PLA and HNTs@Ag3PO4 masterbatch was melt-extruded, hot-air stretched, self-bonded into a web and rolled up to obtain a melt-blown nonwoven fabric HNTs@Ag3PO4 / PLA.
[0061] Comparative Example
[0062] Comparative Example 1
[0063] 1.71 g of Na2HPO4·12H2O was weighed and added to 100 ml of a mixed solution of deionized water and ethylene glycol (the volume ratio of deionized water to ethylene glycol was 80:20). The solution was ultrasonicated for 10 min and magnetically stirred for 30 min to obtain a mixed solution A-1.
[0064] Silver nitrate (AgNO3) particles were ground into fine powder, 2.448 g was weighed, and added to a mixture of 20 ml of deionized water and ethylene glycol (the volume ratio of the two was 13.3:6.7), and magnetically stirred for 30 min to obtain a silver nitrate solution. The silver nitrate solution was slowly added to the mixture A-1 using a peristaltic pump with a flow rate of 2 ml / min, and the reaction was magnetically stirred for 2 h in a light-proof state.
[0065] After the reaction, the reaction solution was centrifuged at 4000 rpm for 5 min, and the solid was washed 3-5 times with ethanol, and then dried at 60°C for 6 hours and ground to obtain pure Ag3PO4 nanoparticles.
[0066] Comparative Example 2
[0067] PLA melt-blown nonwoven fabric was prepared according to the method for preparing melt-blown nonwoven fabric HNTs@Ag3PO4 / PLA in Example 2, with the only difference being that the PLA melt-blown nonwoven fabric was prepared using polylactic acid PLA as raw material.
[0068] PLA was dried in a vacuum oven at 80°C for 12h. It was added to a melt-blown nonwoven machine, and the temperatures of each zone (Ts1, Ts2, Ts3, die head, metering pump and spinneret) were set to 185, 190, 190, 190, 195, 210 and 235°C, respectively, the hot air temperature was 215°C, the curtain speed was 25Hz, and the wind speed was 35Hz. After melt extrusion, hot air stretching, self-bonding into a web and winding, a PLA melt-blown nonwoven fabric was obtained.
[0069] Experimental example
[0070] Experimental Example 1
[0071] The HNTs@Ag3PO4 nanoparticles prepared in Example 1 and the pure Ag3PO4 nanoparticles prepared in Comparative Example 1 were analyzed by scanning electron microscopy (SEM).
[0072] The microstructure was observed using a JEM-7500F scanning electron microscope. The test was performed under the conditions of an accelerating voltage of 5 kV and a current of 10 μA. Figure 1 shown.
[0073] pass Figure 1 It can be seen that during the growth of pure Ag3PO4 nanoparticles, obvious agglomeration will occur, resulting in a serious reduction in its specific surface area, affecting its antiviral performance. By comparison, it was found that the HNTs@Ag3PO4 particles synthesized using HNTs as a carrier can effectively improve the dispersibility of Ag3PO4 particles, reduce agglomeration, and increase its specific surface area.
[0074] Within the same synthesis time, the average particle size of pure Ag3PO4 particles was 559 nm, while the average particle size of Ag3PO4 in the synthesized HNTs@Ag3PO4 particles dropped significantly to 126 nm, indicating that its antiviral performance was improved.
[0075] Experimental Example 2
[0076] The mechanical properties of the melt-blown nonwoven fabric HNTs@Ag3PO4 / PLA prepared in Example 2 and the PLA melt-blown nonwoven fabric prepared in Comparative Example 2 were tested using a universal testing machine. At a tensile speed of 10 mm / min, the stress-strain curve was obtained. Figure 2 shown.
[0077] from Figure 2It can be seen that compared with the melt-blown nonwoven fabric HNTs@Ag3PO4 / PLA, the mechanical properties of PLA melt-blown nonwoven fabric are poor, and the breaking strength and breaking elongation are only 0.15MPa and 1.31%. The mechanical properties of HNTs@Ag3PO4 / PLA melt-blown nonwoven fabric are significantly improved, and the breaking strength and breaking elongation are increased to 0.24MPa and 2.6%.
[0078] Experimental Example 3
[0079] The filtration efficiency and pressure drop of the melt-blown nonwoven fabric HNTs@Ag3PO4 / PLA prepared in Example 2 and the PLA melt-blown nonwoven fabric prepared in Comparative Example 2 were tested using a fully automatic filter material testing machine. At an airflow rate of 32 L / min, HNTs@Ag3PO4 / PLA and the PLA melt-blown nonwoven fabric prepared in Comparative Example 2 filtered dioctyl phthalate DOP aerosols of different particle sizes. The filtration efficiency of the two (Filtration efficiency) changes with the particle size of the DOP aerosol as shown in the following curves: Figure 3 shown.
[0080] Depend on Figure 3 It can be seen that with the increase of the particle size of dioctyl phthalate (DOP) aerosol, the filtration efficiency increases significantly. And the filtration efficiency of HNTs@Ag3PO4 / PLA melt-blown nonwoven fabric is significantly higher than that of PLA melt-blown nonwoven fabric as a whole. This is because HNTs contains SiO2, which is an excellent electret material with strong charge storage capacity, which significantly enhances the electrostatic adsorption of particles by the HNTs@Ag3PO4 / PLA melt-blown nonwoven fabric after electret treatment.
[0081] When the DOP aerosol particle size is 0.3μm, the filtration efficiency of the three-layer HNTs@Ag3PO4 / PLA melt-blown nonwoven fabric is as high as 94.6%, and the resistance is 25.3Pa. The filtration efficiency of the four-layer HNTs@Ag3PO4 / PLA melt-blown nonwoven fabric reaches 98.5%, reaching the filtration efficiency standard of N95. It can effectively protect the human body and also provide a good basis for antiviral experiments.
[0082] Experimental Example 4
[0083] The melt-blown nonwoven fabric HNTs@Ag3PO4 / PLA prepared in Example 2 and the PLA melt-blown nonwoven fabric prepared in Comparative Example 2 were tested for their inactivation of influenza A (H1N1) virus. Figure 4 (a) Figure 4 (c) Cell culture photos of PLA meltblown nonwovens and HNTs@Ag3PO4 / PLA meltblown nonwovens without influenza A (H1N1) virus added; Figure 4 (b) Figure 4 (d) Photos of PLA meltblown nonwoven and HNTs@Ag3PO4 / PLA meltblown nonwoven added with influenza A (H1N1) virus cell culture.
[0084] 200 μL of influenza A (H1N1) virus solution was dripped at multiple points on 2# and 3# HNTs@Ag3PO4 / PLA melt-blown nonwoven fabrics (test samples) and 1#, 2#, and 3# PLA melt-blown nonwoven fabrics (control samples).
[0085] The virus solution was immediately washed out of the 1# control sample using SCDLP (Soya Casein Digest Lecithin Polysorbate Broth) solution.
[0086] The 2# test sample and the 2# control sample were placed under a 200W xenon lamp at a distance of 30 cm. After irradiation for 2 hours, the virus solution was washed out with SCDLP solution.
[0087] Wrap the 3# test sample and 3# control sample with tin foil to protect them from light, place them at room temperature for 2 hours, and wash out the virus liquid with SCDLP solution.
[0088] The virus wash solution obtained above was diluted in a gradient manner and the cells were inoculated with the dilutions of different gradients for TCID50 detection and virus titer determination. The inoculated cells were placed in a 37°C, 5% CO2 incubator for 4-5 days and the cell pathological changes were observed. The results are as follows:
[0089] After the virus solution of the 1# control sample was used to inoculate the cultured cells, no pathological changes were found in the cells under the attack of the virus.
[0090] After the virus solution of the 2# control sample was used to inoculate the cultured cells, the cells were found to have pathological changes under the attack of the virus. After the virus solution of the 2# test sample was used to inoculate the cultured cells, the cells were not found to have pathological changes under the attack of the virus.
[0091] After the virus solution of the 3# control sample was used to inoculate the cultured cells, no pathological changes were found in the cells under the attack of the virus. After the virus solution of the 3# test sample was used to inoculate the cultured cells, no pathological changes were found in the cells under the attack of the virus.
[0092] Verification of cytotoxicity: No. 4 test sample HNTs@Ag3PO4 / PLA melt-blown nonwoven fabric and No. 4 control sample PLA melt-blown nonwoven fabric were rinsed with SCDLP solution only without adding virus solution, and the rinse solution was gradiently diluted and inoculated with cells.
[0093] Depend on Figure 4 (a) Figure 4(c) It can be seen that when influenza A (H1N1) virus was not added, the cell culture growth in the SCDLP solution of PLA melt-blown nonwoven fabric (4# control sample) and HNTs@Ag3PO4 / PLA melt-blown nonwoven fabric (4# test sample) was normal and unaffected, proving that HNTs@Ag3PO4 / PLA melt-blown nonwoven fabric is harmless to cells, can be used safely, and has good biocompatibility.
[0094] Depend on Figure 4 (b) It can be seen that when the virus solution of the 2# control sample was used to inoculate the cultured cells, the cells were found to have lesions under the attack of the virus, proving that the PLA meltblown nonwoven material has no antiviral ability and the killing rate of influenza A (H1N1) virus is 0%.
[0095] Depend on Figure 4 (d) It can be seen that after the virus solution of the 2# test sample was used to inoculate the cultured cells, no cell lesions were found under the attack of the virus, proving that the HNTs@Ag3PO4 / PLA melt-blown nonwoven material has excellent antiviral ability, and the killing rate of influenza A (H1N1) virus is as high as 99.99%.
[0096] The present invention is described in detail above in conjunction with specific embodiments and / or exemplary examples and drawings, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. An antiviral composite polylactic acid, comprising polylactic acid (PLA) and halloysite nanotubes (HNTs) loaded with silver nanoparticles.
2. The antiviral composite polylactic acid according to claim 1, characterized in that: The mass fraction of the silver nanoparticle-loaded halloysite nanotubes in the antiviral composite polylactic acid is 0.6-2.4wt%, preferably 0.7-1.8wt%, and more preferably 0.8-1.2wt%.
3. A method for preparing the antiviral composite polylactic acid according to claim 1, characterized in that: The method melt-blends the halloysite nanotubes loaded with silver nanoparticles with polylactic acid to obtain a composite masterbatch, and then mixes the composite masterbatch with the polylactic acid and melt-blows the mixture to obtain the antiviral composite polylactic acid.
4. The method according to claim 3, characterized in that The method specifically comprises the following steps: Step 1. adding a silver compound solution to a solution containing a precipitant and HNTs, stirring the solution to react, and obtaining halloysite nanotubes loaded with silver nanoparticles; Step 2. melt-blending PLA and halloysite nanotubes loaded with silver nanoparticles to obtain a composite masterbatch; Step 3. Add the composite masterbatch into PLA for melt-blowing to obtain antiviral composite polylactic acid, that is, antiviral composite polylactic acid melt-blown cloth.
5. The method according to claim 3, characterized in that: In step 1, The silver compound is selected from water-soluble silver compounds, The precipitant is selected from one or more of water-soluble phosphates and water-soluble monohydrogen phosphates, In the silver compound solution, the solvent is selected from one or more of water, alcohol solvents, ether solvents and ester solvents, preferably selected from one or more of water and glycol solvents, more preferably a mixed solvent of water and ethylene glycol, the concentration of the silver compound is (0.4-1.2) mol / L, preferably (0.5-1.0) mol / L, more preferably (0.6-0.8) mol / L, In the solution containing the precipitant and HNTs, the solvent is selected from one or more of water, alcohol solvents, ether solvents and ester solvents, preferably selected from one or more of water and glycol solvents, more preferably a mixed solvent of water and ethylene glycol.
6. The method according to claim 3, characterized in that: In step 1, In the solution containing the precipitant and HNTs, the molar mass ratio of the precipitant to the HNTs is (0.002-0.007) mol:0.8 g, preferably (0.003-0.006) mol:0.8 g, and more preferably (0.004-0.005) mol:0.8 g; The molar mass ratio of the silver compound to the HNTs is (0.01-0.06):0.8 g, preferably (0.01-0.04):0.8 g, and more preferably (0.01-0.02):0.8 g.
7. The method according to claim 3, characterized in that In step 1, the average length of the halloysite nanotubes loaded with silver nanoparticles is 100-2000 nm, preferably 400-1000 nm, and more preferably 600-800 nm.
8. The method according to claim 3, characterized in that In step 2, The melt blending temperature is 150-225°C, preferably 160-215°C, more preferably 170-205°C, In the composite masterbatch, the mass fraction of the halloysite nanotubes loaded with silver-containing nanoparticles is 4-18wt%, preferably 6-15wt%, and more preferably 8-12wt%.
9. The method according to claim 3, characterized in that: In step 3, The mass of the composite masterbatch is 4-24% of the total mass of PLA and the composite masterbatch, preferably 6-18%, more preferably 8-12%, The melting temperature is 175-215°C, preferably 180-205°C, more preferably 185-195°C, and the spinning temperature of the spinneret is 220-250°C, preferably 225-245°C, more preferably 230-240°C.
10. A use of the antiviral composite polylactic acid according to claim 1, characterized in that: It is used as meltblown fabric to make protective equipment to filter out new coronaviruses and influenza viruses, such as the influenza A (H1N1) virus.
